Issues in islamic banking : selected papers - Siddiqi, Muhammad Nejatullah (United Kingdom : The Islamic Foundation, 1983)
Business
2004-11-02
Keywords: Islamic banking; Monetary policy; Islamic framework; Islamic economics; Islamic countries